Best Road Trips Midwest & the Great Lakes : escapes on the open road - Baker, Mark (Travel writer); Lonely Planet Global Limited (Lonely Plant, 2022)
Discover the freedom of open roads with Lonely Planet's Midwest & the Great Lakes' Best Road Trips. This trusted travel companion features a collection of amazing drives, from day escapes to multi-week adventures. Follow the Tribal Trails, see Highway 61's vistas, and conquer Chicago. Get to the Midwest & Great Lakes, rent a car, and hit the road! Itineraries for classic road trips plus other lesser-known drives with expert advice to pick the routes that suit your interests and needs. Full-color route maps -- easy-to-read, detailed directions. Detours -- delightful diversions to see the Midwest & Great Lakes' highlights along the way. Link Your Trip -- cruise from one driving route to the next. Insider tips -- get around like a local, avoid trouble spots and be safe on the road - local driving rules, parking, toll roads. Stretch Your Legs -- the best things to do outside the car. Essential infoat your fingertips -- hours of operation, phone numbers, websites, prices. Honest reviews for all budgets -- eating, sleeping, sightseeing, hidden gems that most guidebooks miss. Lavish color photography provides inspiration throughout. Covers Michigan's Gold Coast, the Great River Road, Highway 61, Chicago, Oklahoma's Tribal Trails, the Pioneer Trails, the Black Hills, St Louis, Kansas City, Omaha, and more. The Perfect Choice: Lonely Planet's Midwest & the Great Lakes' Best Road Trips is perfect for exploring the Midwest & Great Lakes via the road and discovering sights that are more accessible by car.
Plan your trip -- Road trips. Black Hills Loop -- The Mighty Mo -- Michigan's Gold Coast -- Highway 61 -- Destinations.
Includes index.
Keywords: Automobile travel -- Middle West -- Guidebooks; Automobile travel -- Lake States -- Guidebooks; Automobile travel; Middle West -- Guidebooks; Lake States -- Guidebooks; Middle West -- Description and travel; Lake States -- Description and travel; Lake States; Middle West; Guidebooks; Guidebooks